A Suboptimal Dual Control Method for the Stochastic Systems with Parameters Drifting. Issue 1 (22nd March 2018) - Yang, Hengzhan; Gao, Song; Qian, Fucai; Huang, Jiaoru
Abstract: This paper proposed a suboptimal dual control method for the stochastic systems with parameters drifting. Based on the consideration of the performance index control and the parameter estimation, the minimum variance of the system output and the estimated covariance matrix of the parameters estimation are both put into the performance index to evaluate the control quality. Furthermore, a dual control strategy is designed which is of the property of learning and control. Simulation results illustrate the effectiveness of the algorithm.